Cultural Policy and Publishing in Ghana: Exploring the Symbiosis Between Policy and Practice - Reuben Agbelengor Glover; Lucy Afeafa Ry-Kottoh; Adolph Hilary Agbo; Michael Ato Essuman (E-Journal of Humanities, Arts and Social Sciences)
This evaluative study provides an in-depth analysis of Ghana’s publishing industry within the context of cultural policy. It explores the symbiosis between national cultural policy, ancillary policies, and its operational dynamics, focusing on how policy directives are implemented in the publishing sector, with emphasis on the mandate of the National Commission on Culture (NCC) as a regulator and facilitator in promoting the growth of local authorship and literary arts through culture. Data was obtained from policy documents and interviews, which were analysed using ontological and epistemological theories of post-positivists, critical realism and constructivist paradigms for public policy analysis. The findings indicate that while the publishing industry’s practices, challenges, and innovations have the potential to influence national development, policymakers and administrators are apathetic towards these dynamics, indicating a disconnect between cultural policy objectives and the realities faced by industry stakeholders. Furthermore, it identified gaps in policy implementation and recommended strategies to enhance the industry’s contribution to national development by establishing links between policy formulation and sector performance. These insights are valuable to policymakers and publishers looking to strengthen the synergy between culture and publishing in Ghana. Ultimately, this study enriches our understanding of publishing as a culturally significant pursuit within a commercial context, highlighting its broader impact and influence.